ELECTRIC-FIELD EFFECTS ON ROTO-VIBRATIONAL TRANSITIONS OF (CD3OH)-C-13 - Telles, E. M.; Moraes, João Carlos Silos [UNESP]; Scalabrin, A.; Pereira, D.; Carelli, G.; Massa, C. A.; Moretti, A.; Strumia, F. (Plenum Publ Corp, 1995)
We used a Stark-Optoacoustic cell and hybrid waveguide resonators to perform an Infrared and Far Infrared Stark Spectroscopy study on some transitions of (CD3OH)-C-13. Different behaviours of the transitions in the presence of a d.c. electric field were observed. The Stark splittings of six FIR laser lines ranging from 34 to 136 MHz/kVcm(-1) were determined. The analysis of the behaviour of the IR and FIR transitions in the presence of the external electric fields gives important and exclusive information on the levels involved in the transitions.
Keywords: STARK SPECTROSCOPY; FAR INFRARED LASER; METHANOL